Analisis Desain Pengembangan Model Bisnis pada Perusahaan Pengalengan Ikan dengan Metode Bussiness Model Canvas (BMC) pada PT. ABC - Annisa, Lolanda Hamim; Ningrum, Siti Fatimah Ayu Setiya; Wulansari, Zabna Eka (Journal of Agribusiness Science and Rural Development, 2023)
The Business Model Canvas (BMC) helps companies create their business models based on nine blocks of needs identification. BMC is a tool that provides a clear view of what a company needs to achieve and focuses on the strategic elements that are most important and will have the greatest impact on the business. In this research, we took a case study at PT. ABC to map the BMC of existing business processes in the company. In this research, we will focus on the elements in the blocks at PT. ABC will be designed in this research. Then compared between the nine blocks in BMC and researchers focused on developments that could be carried out in business development. The research results show that the mapping on BMC is expected by PT. ABC implements online ordering to expand the Company's expansion and also expand market share segmentation by adding supermarkets and retail stores as product distributors.